Optical Rules to Mitigate the Parallax-Related Registration Error in See-Through Head-Mounted Displays for the Guidance of Manual Tasks - Vincenzo Ferrari; Nadia Cattari; Sara Condino; Fabrizio Cutolo (Multimodal Technologies and Interaction, 2024)
Head-mounted displays (HMDs) are hands-free devices particularly useful for guiding near-field tasks such as manual surgical procedures. See-through HMDs do not significantly alter the user’s direct view of the world, but the optical merging of real and virtual information can hinder their coherent and simultaneous perception. In particular, the coherence between the real and virtual content is affected by a viewpoint parallax-related misalignment, which is due to the inaccessibility of the user-perceived reality through the semi-transparent optical combiner of the OST Optical See-Through (OST) display. Recent works demonstrated that a proper selection of the collimation optics of the HMD significantly mitigates the parallax-related registration error without the need for any eye-tracking cameras and/or for any error-prone alignment-based display calibration procedures. These solutions are either based on HMDs that projects the virtual imaging plane directly at arm’s distance, or they require the integration on the HMD of additional lenses to optically move the image of the observed scene to the virtual projection plane of the HMD. This paper describes and evaluates the pros and cons of both the suggested solutions by providing an analytical estimation of the residual registration error achieved with both solutions and discussing the perceptual issues generated by the simultaneous focalization of real and virtual information.